Exploring The Benefits And Challenges Of Interprofessional Collaboration In Nursing (Journal of Namibian Studies : History Politics Culture, 2022)
An efficient interprofessional cooperation among healthcare workers is necessary to guarantee the delivery of high-quality patient care. Interprofessional education (IPE) enhances collaboration and cooperation among healthcare professionals in their everyday practice, leading to improved teamwork. However, there are several obstacles to the successful application of IPE. The objective is to examine how IPE should be structured and integrated into medical and nursing education programs in order to maximize students' influence on IPC. The experts identify a greater number of factors that facilitate interprofessional education (IPE) among medical and nursing students, as opposed to those that hinder it. The four main justifications for IPE include: fostering interprofessional thinking and doing, gaining shared knowledge, facilitating useful information and knowledge interchange, and promoting mutual understanding. The primary obstacles to IPE are collaboration and synchronization of the courses across the two professions. Regarding the impacts of Interprofessional Education (IPE) on Interprofessional Collaboration (IPC), experts discussed potential enhancements at both the patient and professional levels. Anticipated is an enhanced kind of patient-centered care that is rooted on greater mutual comprehension and coordinated collaboration within interprofessional healthcare teams. In order to effectively establish Interprofessional Education (IPE) for healthcare and nursing students, it is necessary to get support and approval from both the medical and nursing schools. To summarize, IPE facilitates collaboration among the medical and nursing professions. Proficiency in interprofessional interaction and an understanding of responsibilities will be essential prerequisites for enhancing cooperative patient-centered care. It is necessary to conduct prospective intervention research to analyze the unique effect of IPE on individuals, caregivers, and professionals alike.